The role played by ailanthone in inhibiting bone metastasis of breast cancer by regulating tumor-bone microenvironment through the RANKL-dependent pathway - Yajun Wang; Yajun Wang; Zeyuan Zhong; Zeyuan Zhong; Miao Ma; Miao Ma; Yannan Zhao; Yannan Zhao; Chongjing Zhang; Chongjing Zhang; Zhi Qian; Biyun Wang; et al. (Frontiers Media S.A., 2023)
Introduction: Bone metastasis of breast cancer (BC) is a process in which the disruption of the bone homeostatic microenvironment leads to an increase in osteoclast differentiation. Ailanthus altissima shows an inhibitory effect on osteoclast differentiation. Ailanthone (AIL) refers to a natural compound isolated from Ailanthus altissima, a Chinese herbal medicine, and has effective anti-tumor activity in numerous cell lines. Its impact on bone metastases for BC is yet unclear.Methods: We measured the effect of AIL on MDA-MB-231 cells by wound healing experiments, Transwell and colony formation experiment. Using the Tartrate-resistant Acid Phosphatase (TRAP) staining tests, filamentous (F-actin) staining and bone resorption test to detect the effect of AIL on the osteoclast cell differentiation of the Bone Marrow-derived Macrophages (BMMs), activated by the MDA-MB-231 cell Conditioned Medium (MDA-MB-231 CM) and the Receptor Activator of Nuclear factor-κB Ligand (RANKL),and to explore its possibility Mechanisms. In vivo experiments verified the effect of AIL on bone destruction in breast cancer bone metastasis model mice.Results:In vitro, AIL significantly decrease the proliferation, migration and infiltration abilities of MDA-MB-231 cells at a safe concentration, and also reduced the expression of genes and proteins involved in osteoclast formation in MDA-MB-231 cells. Osteoclast cell differentiation of the BMMs, activated by MDA-MB-231 CM and RANKL, were suppressed by AIL in the concentration-dependent manner. Additionally, it inhibits osteoclast-specific gene and protein expression. It was noted that AIL inhibited the expression of the osteoclast differentiation-related cytokines RANKL and interleukin-1β (IL-1β) that were secreted by the MDA-MB-231 cells after upregulating the Forkhead box protein 3 (FOXP3) expression. Furthermore, AIL also inhibits the expression of the Mitogen-Activated Protein Kinase (MAPK), Phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT), and Nuclear factor-κB Ligand (NF-κB) signaling pathways, which then suppresses the MDA-MB-231CM-induced development of Osteoclasts.Conclusion: Our study shows that AIL blocks osteoclast differentiation in the bone metastasis microenvironment by inhibiting cytokines secreted by BC cells, which may be a potential agent for the treatment of BC and its secondary bone metastasis.